(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: The changes in the morbidity and mortality profile of the elderly population brought several challenges for health care services that need to be prepared, articulated and planned based on sociodemographic, clinical and behavioral determinants, which has been associated with Fragility Syndrome. Objective: To analyze the factors associated with Frailty Syndrome in the elderly in the context of Primary Care, cooperating in redirecting care practices in health care for the elderly. Methods: This is a quantitative, population-based, cross-sectional study. The dependent variables were measured using the Clinical Functional Vulnerability Index-20, composed of twenty questions covering age, self-perceived health, activities of daily living, cognition, mood, mobility, communication and multiple comorbidities. Results: Among the 244 respondents, 36.89% are in the frailty risk group, 36.1% in robust elderly people and 27% are in the frailest group. Conclusion: It can be concluded that it is essential to implement strategies and actions to stimulate active aging, enabling the early detection of conditions that can generate disabilities.